2017
DOI: 10.1158/1078-0432.ccr-17-0373
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Squamous Cell Carcinomas Are Characterized by a Stable Immune Signature Within the Primary Tumor Over Time and Space

Abstract: Genetic and morphologic heterogeneity is well-documented in solid cancers. Immune cells are also variably distributed within the tumor; this heterogeneity is difficult to assess in small biopsies, and may confound our understanding of the determinants of successful immunotherapy. We examined the transcriptomic variability of the immunologic signature in head and neck squamous cell carcinoma (HNSCC) within individual tumors using transcriptomic and IHC assessments. Forty-four tumor biopsies from 16 HNSCC patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 33 publications
3
19
0
1
Order By: Relevance
“…In this study we have used an immune signature reported by Wood et al, due to its high stability in HNSCC specimens (Suppl. Figure 3b) [26]. We found that low expression of TMPRSS2 signi cantly associates with low immune signature in TCGA HNSCC patients' cohort ( Fig.…”
Section: Ace2 and Tmprss2 Expression In Hnscc Patientsmentioning
confidence: 60%
“…In this study we have used an immune signature reported by Wood et al, due to its high stability in HNSCC specimens (Suppl. Figure 3b) [26]. We found that low expression of TMPRSS2 signi cantly associates with low immune signature in TCGA HNSCC patients' cohort ( Fig.…”
Section: Ace2 and Tmprss2 Expression In Hnscc Patientsmentioning
confidence: 60%
“…Fig. 3 b) [ 28 ]. We found that low expression of TMPRSS2 significantly associates with low immune signature in TCGA HNSCC patients’ cohort (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Multiplex immunohistochemistry (MxIHC) was performed on FFPE samples from the HNSCC cohort (Bulk RNA-seq and analysis; ref. 38), where tissue was available (n ¼ 16; Research Ethics Committee reference 09/H0501/90). Staining and image processing was performed as previously with minor alterations (41).…”
Section: Histologic Analysismentioning
confidence: 99%